Tangible and Intangible Legacy of the 19th Century Zappas Olympics and their Implications for Contemporary Sport Tourism - Margaritis George; Rozmiarek Mateusz; Malchrowicz-Mosko Ewa (Sciendo, 2017)
As has been shown in the article, the Zappas Olympics generously contributed to the revival of the Olympic Games in the nineteenth century. The course of these competitions has been described, and a brief summary of Zappas's work, which does not often attract a lot of attention in, for example, Polish academics, has also been made. The fact that the Zappas Olympics mainly enhanced the national identity of the Greeks following Turkish captivity has also been highlighted. The Zappas Olympics allowed the Greeks to become more familiar with sports and fair play. The knowledge that the Greeks acquired from the organization of this event was useful for the organization of the first modern Olympic Games in Athens. These days, material remains of this event serve touristic and cultural functions. The significance of such facilities as the Zappeion and the Panathenaic Stadium have also been underlined. For example, the Zappeion and the Panathenaic Stadium host cultural events and welcome tourists interested in sports history or Greek culture. These are the authorities responsible for touristic policy in Greece and they may decide whether such historic sites and sporting facilities will be included in thematic routes for tourists. According to the authors of the present paper, these sites may effectively compete with mass and recreational attractions in Greece.